The construction of news values in online media sexual violence' discourse - Reza Safitri; Rachmat Kriyantono; Hanindita Basmatulhana (Jurnal Studi Komunikasi, 2024)
News values refer to a set of criteria intended to evaluate the newsworthiness of an event, hence determining its suitability for publication. For instance, a case of sexual violence in Indonesia received significant attention and is considered noteworthy, warranting its reporting. This study aims to discover the significance of news articles pertaining to sexual violence and determine the linguistic construction of news value within the context of online media platform detik.com. The researchers collected headlines and lead paragraphs from all 27 online news articles published throughout July 2022 that were selected since July had the highest number of sexual violence incidents. The articles were qualitatively analysed through discursive news value analysis technique (DNVA) which examines the connotations of diction choices and the impact on readers’ understanding. The study revealed that six out of the 10 news values were present in reports on sexual violence in Indonesia. These news values include personalisation, proximity, eliteness, positivity, unexpectedness, and timeliness. This study also shows that news articles share an emphasis on personalisation and proximity. Research limitation includes the process of defining news values and subjectively evaluating sources based on the definitions.